Muddy Decisions: Gold in the Chocó, Colombia. Issue 4 (December 2015) - Tubb, Daniel
Highlights: Why do Afro-descendant miners in Colombia's northwest Chocó department, who used hand tools and techniques, often invite outsiders, who used heavy machinery and mercury, to work their mines? Reasons include: familial pressure over land, profit sharing, high prices, access to gold, and dangerous working conditions. Abstract: As gold prices rose between 2002 and 2012, Afro-descendant gold miners confronted illegal outsider-owned gold mines on their land in Colombia's northwest Chocó department. This article examines why these Afro-descendant miners, who used hand tools and techniques, often invited the outsiders, who used heavy machinery and mercury, to work their mines. Their reasons included: familial pressure over land, profit sharing, high prices, access to gold, and dangerous working conditions. The decision to invite in the outsiders complicates the conventional narrative of a coercive relationship between outsiders and Afro-descendant communities, even as the relationship produced worse than expected outcomes for both sides.